Effect of a low-cost and highly efficient passivator synthesized by alkali-fused fly ash and swine manure on the leachability of heavy metals in a multi-metal contaminated soil. (September 2021) - Wang, Kaifeng; Peng, Na; Zhao, Ping; Chen, Meiqin; Deng, Fucai; Yu, Xiaolong; Zhang, Dongqing; Chen, Junfeng; Sun, Jianteng
Abstract: Soil pollution, caused by heavy metals, is an environmental problem that requires an urgent solution in China. Chemical passivation is a technology that uses various passivators to reduce the availability of heavy metals in soil and realize the remediation of contaminated soil. In this study, we examined the effects of fly ash (FA), alkali-fused fly ash (AFFA), swine manure biochar (SB), and modifying biochar (MB) on the leachability of Cu, Zn, Pb, and Cd via soil culture experiments. The results showed that the addition of AFFA, SB, and MB significantly reduced the extractable contents of Cu, Pb, and Cd in the soil. AFFA and MB had the best passivation effect, followed by SB and FA. The passivation effect on Pb was the best, followed by that on Cu and Cd. AFFA modification significantly improved the passivation effect of MB on Cu, Pb, and Cd in composite contaminated soil. With the addition of 3% MB, the Pb, Cu, and Cd extracted by TCLP decreased by 95.7, 74.1, and 59.1%, respectively. Correlation analysis, Fourier transform infrared spectrometry, scanning electron microscopy, and energy-dispersive X-ray spectroscopy showed that the passivation mechanism is mainly due to an increase in the soil pH, silicate content, and cohesiveness. The soil culture experiments in this study proved that MB is a low-cost and highly efficient organic-inorganic composite passivator for multi-metal contaminated soils. Graphical abstract: Image 1 Highlights: New organic-inorganic composite passivator synthesized by alkali-fused fly ash and swine manure. Modifying biochar has a good passivation effect on Pb, Cu, and Cd in polluted soil. Heavy metal passivation via alkalinity and silicate introduced by alkali-fused fly ash. Modifying biochar an efficient passivator for multi-metal contaminated soil.